Synthesis and Antibacterial Activity of Tetrahydrocurcuminoids - Venkateswarlu, Somepalli; Rambabu, Madabattula; V. Subbaraju, Gottumukkala; Satyanarayan, S. (Asian Journal of Chemistry, 2010)
The naturally occurring curcuminoids, curcumin (1), demethoxycurcumin (2) bisdemethoxycurcumin (3) were synthesised and converted into their tetrahydro derivatives (4-6) respectively. Compounds (4-6) showed enhanced antibacterial activity compared to naturally occurring curcuminoids.